First Case Report Associating Gemcitabine with Hypersensitivity Reaction in a Patient with Pancreatic Cancer - Saif, Muhammad Wasif; Chakerian, Paula; Kaley, Kristin; Lamb, Lynne (JOP. Journal of the Pancreas, 2010)
No abstract available. Image: Ball-and-stick model of the protonated gemcitabine cation and the nearest chloride anion (Author: Benn Mils; Wikimedia Commons).